CONTRIBUTION OF SEAWEED CULTIVATION BUSINESS IN EXPANDING JOB OPPORTUNITY AND IMPROVING COMMUNITY WELFARE IN THE DISTRICT OF PANGKAJENE AND ISLANDS - Abidin S, Zainal (Jurnal Pertahanan dan Bela Negara, 2019)
This study entitled Business Contribution of Seaweed Cultivation in Expanding Employment and Improving Community Welfare in Pangkajene and Islands Districts. The formulation of the problem raised is how the contribution of seaweed cultivation in the Pangkajene and Islands Regency in order to expand employment and improve community welfare and what factors hinder seaweed cultivation in Pangkajene and Islands Districts. This research use desciptive qualitative approach. The results showed that the contribution of seaweed cultivation in Pangkajene and Islands Regency was based on the findings that seaweed farming could improve the welfare of the community in the Pangkajene and Islands regencies. So that the utilization of seaweed in Pangkajen district can then be developed towards the commercial sector to be exported and traded as raw material for the manufacture of agar-agar or carrageenan. Factors that hamper seaweed cultivation in Pangkajene and Kepulauan Regency are related to providing business financing and business capital and natural factors because seaweed cultivation depends on seasons and inadequate seeds, so that seeds and capital are needed so that seaweed cultivation can be developed. Keywords: contribution, seaweed cultivation, community welfare.